[Discussion of An Empirical Study of the Role of Accounting Data in Performance Evaluation]: A Reply - Hopwood, Anthony G. (Journal of Accounting Research, 1972)
Anthony G. Hopwood, [Discussion of An Empirical Study of the Role of Accounting Data in Performance Evaluation]: A Reply, Journal of Accounting Research, Vol. 10, Empirical Research in Accounting: Selected Studies 1972 (1972), pp. 189-193